l-Arginine Improves Sperm Motility in Threatened Coruh Trout Salmo coruhensis (Teleostei: Salmonidae) - Kocabas, Mehmet; Kutluyer, Filiz; Erisir, Mine; Benzer, Fulya (Springer International Publishing Ag, 2019)
l-arginine is a versatile amino acid and precursor of nitric oxide that provides protection for preventing free radical damage. Herein, experiments were designed to clarify the effect of l-arginine supplementation on the sperm motility of a threatened trout, Coruh trout Salmo coruhensis. Activation solution was supplemented with levels of 0mM (Control), 2mM, 4mM, and 8mMl-arginine, and motility and survival of sperm cells were assessed. The selected concentrations were determined according to results of our preliminary experiments. The sperm motility rates at l-arginine concentrations of 0, 2, 4, and 8mM were 73.33 +/- 5.77%, 76.67 +/- 5.75%, 80.01 +/- 0.01%, and 90.00 +/- 0.05%, respectively; notility durations were 21.67 +/- 2.08, 32.33 +/- 3.79, 32.67 +/- 1.15, and 37.00 +/- 6.38s, respectively. Significant effect of l-arginine supplementation was determined on the percentage and duration of motile spermatozoa (p<0.05). The maximum increment was evoked at the greatest concentration (8mM). Here, we showed that l-arginine supplement can improve sperm motility of S. coruhensis.
Keywords: Amino acid; Spermatozoa; Trout; Nitric oxide